Contrast-enhanced ultrasound and shear wave elastography in the diagnosis of ACR TI-RADS 4 and 5 category thyroid nodules coexisting with Hashimoto’s thyroiditis - Wang, Bin; Ou, Xiaoyan; Yang, Juan; Zhang, Haibo; Cui, Xin-Wu; Dietrich, Christoph F.; Yi, Ai-Jiao (Frontiers in Oncology, 2023)
Objective This study aims to evaluate the value of contrast-enhanced ultrasound (CEUS), shear wave elastography (SWE), and their combined use in the differentiation of American College of Radiology (ACR) thyroid imaging reporting and data system (TI-RADS) 4 and 5 category thyroid nodules coexisting with Hashimoto’s thyroiditis (HT). Materials and methods A total of 133 pathologically confirmed ACR TI-RADS 4 and 5 category nodules coexisting with HT in 113 patients were included; CEUS and SWE were performed for all nodules. The sensitivity, specificity, negative predictive value (NPV), positive predictive value (PPV), accuracy, and the area under the receiver operating characteristic curve (AUC) of the SWE, CEUS, and the combined use of both for the differentiation of benign and malignant nodules were compared, respectively. Results Using CEUS alone, the sensitivity, specificity, PPV, NPV, and accuracy were 89.2%, 66.0%, 81.3%, 78.6%, and 80.5%, respectively. Using SWE alone, Emax was superior to Emin, Emean, and Eratio for the differentiation of benign and malignant nodules with the best cutoff Emax >46.8 kPa, which had sensitivity of 65.1%, specificity of 90.0%, PPV of 91.5%, NPV of 60.8%, and accuracy of 74.4%, respectively. Compared with the diagnostic performance of qualitative CEUS or/and quantitative SWE, the combination of CEUS and SWE had the best sensitivity, accuracy, and AUC; the sensitivity, specificity, PPV, NPV, accuracy, and AUC were 94.0%, 66.0%, 82.1%, 86.8%, 83.5%, and 0.80 (95% confidence interval: 0.713, 0.886), respectively. Conclusion In conclusion, CEUS and SWE were useful for the differentiation of benign and malignant ACR TI-RADS 4 and 5 category thyroid nodules coexisting with HT. The combination of CEUS and SWE could improve the sensitivity and accuracy compared with using CEUS or SWE alone. It could be a non-invasive, reliable, and useful method to differentiate benign from malignant ACR TI-RADS 4 and 5 category thyroid nodules coexisting with HT.